Impact of pre‐emptive rapid testing for glucose‐6‐phosphate dehydrogenase deficiency prior to rasburicase administration at a tertiary care centre: A retrospective study. Issue 9 (2nd May 2022) - Ganapathi, Mythily; Campbell, Peter; Ofori, Kenneth; Aggarwal, Vimla; Francis, Richard O.; Kratz, Alexander
Abstract : Aims: Glucose‐6‐phosphate dehydrogenase (G6PD) deficiency, the most common enzymopathy in humans, can cause acute haemolysis resulting from exposure to certain medications, chemicals, infections and fava beans. Rasburicase, used to manage elevated uric acid levels in the oncologic emergency of tumour lysis syndrome, is one such drug. The US Food and Drug Administration (FDA) recommends testing of G6PD status prior to rasburicase administration for patients at higher risk for G6PD deficiency. Methods: We performed a retrospective chart review of all oncology patients for whom a semi‐quantitative biochemical test for detecting G6PD deficiency was performed prior to rasburicase administration over a 2.5‐year period, in a large academic metropolitan hospital. Results: We identified 16 out of 260 tested individuals as G6PD‐deficient (6.1%), including six females. On average, test results were electronically available to health care providers within 4 hours of sample collection, with most results available within 2–3 hours. Four G6PD‐deficient patients developed elevated uric acid levels. Two of the G6PD‐deficient patients were treated with rasburicase, and subsequently developed haemolysis, which was appropriately managed. Conclusion: In summary, by providing information about G6PD status with a rapid turnaround time, we have taken a significant step towards personalized medicine in our institution. In spite of the test implementation, two out of four G6PD‐deficient patients, who were no longer candidates for rasburicase use, still received the drug, highlighting the need for improved provider education.